Minimally invasive approach to esophageal lipoma. Issue 7 (31st July 2020) - Bernardi, Daniele; Ferrari, Davide; Siboni, Stefano; Porta, Matteo; Bruni, Barbara; Bonavina, Luigi
Abstract: Esophageal lipoma is a rare neoplasm with heterogeneous and sometimes life-threatening clinical presentation. We report the case of two patients, a 77-year-old man and a 69-year-old woman presenting with heartburn and dysphagia, and with recurrent vomiting and asphyxia, respectively. Upper gastrointestinal endoscopy and computed tomography were highly suggestive of the diagnosis of esophageal lipoma and identified an intramural and an intraluminal pedunculated mass originating, respectively, from the distal and the cervical esophagus. The first patient was treated by laparoscopic transhiatal enucleation and the second by transoral endoscopic resection under general anesthesia. Both had an uneventful postoperative course and were discharged home on postoperative day 2. Minimally invasive excision of esophageal lipoma is feasible and effective. It may be life-saving in patients with pedunculated tumors who suffer from intermittent regurgitation of a bulky polypoid mass in the mouth causing asphyxia.